UPAYA PEMERINTAH INDONESIA DALAM MEMPROMOSIKAN KEBUDAYAAN INDONESIA DI FORUM INTERNASIONAL : World Culture Forum Tahun 2013 & 2016 - Fitria Amani (2020)
Political, economic and defense issues have become a phenomenon of International Relations lately. But seeing the condition of the world which is in the era of globalization, then culture is an important factor carried out by the State as mainstreaming in sustainable development. So with full awareness of the diversity of cultures that Indonesia has, Indonesia has delivered to be the host of a cultural forum, the World Culture Forum. Cultural diplomacy can be interpreted as an attempt by a country to achieve its national interests through the cultural dimension. The Indonesian government has tried to conduct cultural diplomacy to promote the culture of Indonesia in various ways such as Bilateral Meetings, Cultural Visits, Cultural Fairs, etc. so that Indonesian culture can be recognized by the world community and not lost or eroded by the current of globalization. In addition, the Government of Indonesia also conducts various kinds of symposiums with different themes with a view to exploring the potential for cultural diversity in the world. Various efforts have been made by the Government of Indonesia in order to promote Indonesian culture to be recognized by the world community and this will lead Indonesia to become a home country of world culture, so that it is hoped that Indonesia will continue to be a host country from holding international cultural activities.